Modern alchemy: Collaboration and the value of social capital. Issue 1 (1st March 2015) - Padovani, Clio; Whittaker, Paul
This industry report focuses on the collaboration between Teixidors, a Spanish hand-weaving company and Zuzunaga design studio. It aims to draw attention to collaborative partnerships as a way of enhancing craft practice and product innovation. An interesting feature of the topic is how the maintenance of local knowledge economies and the enhancement of specialist and traditional community skills can contribute to a model of sustainable business. The report is underpinned by research developed through Plustex, a three-year European Union-funded project. Knowledge was gathered through study visits to European textile SMEs and theoretical review of regional policies designed to facilitate competitiveness in the European textile and clothing sector. The textile collection featured in the report, 'Integrate: Time and Space', evidences important factors that can positively contribute to the competitiveness of an enterprise: sustainable social capital, collaboration and the creation of shared value.